2020
DOI: 10.3390/brainsci10120962
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Resistant Depression in a Real-World Setting: First Interim Analysis of Characteristics, Healthcare Resource Use, and Utility Values of the FondaMental Cohort

Abstract: Background: Major depressive disorder (MDD) is among the most common psychiatric disorders. One-third of patients are usually unresponsive to several lines of treatment. This study aimed to describe the FondaMental French cohort of patients with treatment-resistant depression (TRD) and to estimate utility and healthcare resource use outcomes. Methods: Patients with TRD were evaluated prospectively over four years (baseline, 6, 12, 18, 24, 36 and 48 months) in a real-world clinical setting. Interim analyses foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Confirming the high burden of TRD, our patients showed low quality of life and poor functioning, together with a substantial degree of disability. In particular, we observed a mean utility value derived from EQ-5D-5L of 0.44, similar to that reported in a recently published French TRD cohort (26). The much lower employment rate in our study (34%, which increased to 39% when calculated excluding retired patients) compared to that reported for the Italian population (63% among individuals aged 20-64 years in 2018 according to the Italian National Institute of Statistics) is not unexpected and confirms the personal and social burden of TRD.…”
Section: N = 89supporting
confidence: 88%
See 2 more Smart Citations
“…Confirming the high burden of TRD, our patients showed low quality of life and poor functioning, together with a substantial degree of disability. In particular, we observed a mean utility value derived from EQ-5D-5L of 0.44, similar to that reported in a recently published French TRD cohort (26). The much lower employment rate in our study (34%, which increased to 39% when calculated excluding retired patients) compared to that reported for the Italian population (63% among individuals aged 20-64 years in 2018 according to the Italian National Institute of Statistics) is not unexpected and confirms the personal and social burden of TRD.…”
Section: N = 89supporting
confidence: 88%
“…Real-world evidence on patients with TRD is scarce (15,24,25), especially from European countries (26), and mainly derived from retrospective studies based on administrative databases or electronic health records (27)(28)(29). Within these studies, data on prescribing patterns and illness outcome are sparsely reported (24)(25)(26)30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For MAUIs, such as the EQ-5D-5L, derivation of utility values using the mapping process is a reflection, in part, of the country-specific culture and how individuals value different health-related issues. 3 Methods designed to directly elicit utility values for aspects of single diseases suffer from several analogous limitations, as well as methodological issues, particularly for certain comorbidities whose impact varies, such as the diurnal pattern of rheumatoid arthritis, 101 episodes of depression, 102 or of a limited duration, such as surgical wounds. 9 Consequently, while these values are certainly very useful, the methodology underpinning their estimation should still be judged as a “work in progress,” despite a positive future outlook.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…Despite the existence of validated measures of depressive symptom severity, Rizvi reported that only 25% of doctors in their study used them. While some studies on TRD use standardized scales to assess improvement [28,31,62], others use doctors' evaluations [29] or data regarding treatment found in administrative databases [23,31,32,63]. Our project was based on real-world evidence, and its aim was to reflect decisions made by psychiatrists in practice.…”
Section: Strengths and Limitationsmentioning
confidence: 99%